The impact of psychosocial factors on the risk of erectile dysfunction and inhibition of sexual desire in a sample of the Brazilian population - Abdo, Carmita Helena Najjar; Oliveira Júnior, Waldemar Mendes de; Moreira Júnior, Edson; Abdo, João Afif; Fittipaldi, João Antônio Saraiva (São Paulo Medical Journal, 2005)
CONTEXT: Sexual dysfunctions can have origins in physical, psychological and psychosocial factors. OBJECTIVE: To describe the frequency of erectile dysfunction (ED) and female inhibition of sexual desire (ISD) in a Brazilian sample, and to estimate the risks of these dysfunctions. TYPE OF STUDY: Non-random survey. SETTING: Ten Brazilian cities. METHODS: 2,835 subjects (53% women) aged over 18 years answered a questionnaire about their general health and sex life. The chi-squared test and multivariate logistic regression were used. Values of p 0.05 were considered signiﬁcant. RESULTS: The women’s average age was 36.6 years (± 13.3) and the men’s was 39.5 (± 13.3). 14.7% of men presented moderate/complete ED and 34.6% of women presented ISD. Depression was mentioned by 16.8% of men and 29.7% of women. The chances of having ED and ISD were higher for subjects who had had lower school attainment. Lack of a job and depression gave rise to 1.5 times (95% CI: 1.0 – 2.3) and 1.9 times (95% CI: 1.2 – 3.0) greater chances of ED respectively. Compared with men aged up to 25 years, those aged 41-60 had 1.9 times (95% CI: 1.0 – 3.4) and those aged 61 and over had 5.4 times (95% CI: 2.3 – 12.6) greater risk of ED. For women, lack of a job gave rise to 1.5 times (95% CI: 1.1 – 1.9) greater chance of ISD; depression was not associated with higher risk. Compared with women aged up to 25 years, those aged 41-60 and 61 or over had, respectively, 2.9 times (95% CI: 2.0 – 4.1) and 7.5 times (95% CI: 3.0 –18.6) greater risk of ISD. DISCUSSION: Increasing unemployment has affected the whole population, but especially those with lower levels of school attainment. Such levels are positively linked with presence of sexual dysfunctions. CONCLUSION: Lack of jobs, age and low school attainment are risks for the sexual dysfunctions studied. Depression increased the risk of ED but not female ISD.